KOMPETISI DUA VARIETAS WIJEN (SESAMUM INDICUM L.) DENGAN DUA VARIETAS JAGUNG (ZEA MAYS L.) YANG BERBEDA TAMPILAN MORFOLOGI PADA SISTEM TUMPANGSARI - Yason E. Benu (Partner, 2013)
Competition of two sesame varieties (Sesamum indicum L.) and two Maize Zea mays L.)varieties with different fenotypein intercropping System. The experiment was conducted in the Experimental and Development Garden (KP4) of the University of Gadjah Mada in Kalitirto Berbah, Sleman, from September to December 2001. The objective of the study was to find out the combination of sesame varieties that suitable for intercropping with maize. A strip plot design was used with three replications. The factorial treatment consisted of two factors. The first factor was sesame varieties (Sumberrejo 1 and Sumberrejo 2). The second factor was maize varieties (Hibrida and Lamuru). In each replication, sesame and maize varieties were planted as monocultures. The plot size was 4 m x 6 m, sesame and maize plant spacing were 0,50 m x 0,25 (Sumberrejo 1), 0,45 m x 0,20 m (Sumberrejo 2) and 1,0 m x 0,20 m (Hibrida and Lamuru) respectively. The result showed that the highest relative yield total (RYT) in intercropping sesame and maize was obtained from Sumberrejo 2 and Lamuru at 1,26 while the lowest RYT was obtained from Sumberrejo 2 and Hibrida at 1,32. RYT value of the intercropping system was more than one which is considered as efficient in land use. Area TimeÂ  Equivalent Ratio (ATER) showed that intercropped Sumberrejo 1 and Hibrida has efficiently combination of the land (time and area). Index aggresivity showed that maize dominant for sesame on the intercropping maize and sesame. Competition ratio showed that intercropped combination Hibrida and Sumberrejo 1 have the lowest competition ratio. Keywords: Competition, Sesame, Maize, Varieties, Intercropping